Astigmatic Changes in Sutureless Small Incision Cataract Surgery - Yadav, Roshan Dev; Bajracharya, Kabindra; Shrestha, Neelam; Joshi, Kriti; Gupta, Aman Kumar (Birat Journal of Health Sciences, 2021)
Introduction: Cataract is the main cause of bilateral blindness in Nepal. Surgery is the accepted treatment option for cataract with Small incision Cataract Surgery (SICS) and Phacoemusification being the common procedures being performed with comparable results. Corneal astigmatism has been a byproduct of cataract surgery since the first limbal incision was made with improved techniques. Self-sealing scleral pocket incisions are stable and provides early healing, faster visual restoration and more importantly superior astigmatism control. A variety of scleral incisions are being used in manual SICS, with the aim of keeping the post-operative astigmatism to a minimum. Despite having many techniques of scleral incision, there have been only few studies which compares surgical induced astigmatism (SIA) between them Objective: To determine surgical induced astigmatism following frown, chevron and straight incision forms in suture-less small incision cataract surgery(SICS). Methodology: A prospective study was done on a total of 120 patients aged 40years and above with senile cataract. The patients were randomly divided into three groups where each group received specific incision- Straight, Frown and Chevron. SICS with intraocular lens (IOL) implantation was performed. The patients were compared on 2 weeks and 6 weeks post operatively for uncorrected visual acuity (UCVA), best corrected visual acuity (BCVA) and keratometric reading. Surgical induced astigmatism (SIA) was calculated using the SIA calculator version 2.0. The study was analysed using SPSS version 20.0. Results: At 6 weeks UCVA of 6/18-6/6 was attained by 63.41%, 78.94% and 84.61% of patients in group straight, frown and chevron. However about 97% of patients attained BCVA of 6/18-6/6 in all three groups. Mean SIA was least in Chevron group (0.30 D ± 0.16) and was most in the straight group (1.22 D ±0.36) which was statistically significant. Conclusion: Chevron incision induces the least astigmatism compared to frown and straight incision.